Glycopeptide Hypersensitivity and Adverse Reactions - Vanthida Huang; Nicola A. Clayton; Kimberly H. Welker (MDPI AG, 2020)
Glycopeptides, such as vancomycin and teicoplanin, are primarily used in the treatment of methicillin-resistant Staphylococcus aureus (MRSA) infections, such as cellulitis, endocarditis, meningitis, pneumonia, and septicemia, and are some of the most commonly prescribed parenteral antimicrobials. Parenteral glycopeptides are first-line therapy for severe MRSA infections; however, oral vancomycin is used as a first-line treatment of Clostridioides difficile infections. Also, we currently have the longer-acting lipoglycopeptides, such as dalbavancin, oritavancin, and telavancin to our armamentarium for the treatment of MRSA infections. Lastly, vancomycin is often used as an alternative treatment for patients with β-lactam hypersensitivity. Common adverse effects associated with glycopeptide use include nephrotoxicity, ototoxicity, and Redman Syndrome (RMS). The RMS is often mistaken for a true allergy; however, it is a histamine-related infusion reaction rather than a true immunoglobulin E (IgE)-mediated allergic reaction. Although hypersensitivity to glycopeptides is rare, both immune-mediated and delayed reactions have been reported in the literature. We describe the various types of glycopeptide hypersensitivity reactions associated with glycopeptides and lipoglycopeptides, including IgE-mediated reactions, RMS, and linear immunoglobulin A bullous dermatosis, as well as describe cross-reactivity with other glycopeptides.